Pola Konsumsi Siaran Televisi Di Denpasar: Statistik Deskriptif - Ras Amanda G, Ni Made; Yuri Cahyani, Dewi (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 2, Agustus 2015 (pp. 113-216)DO - 10.24843/JEKT.2015.v08.i02.p03, 2015)
Nowadays television has become the most favorite media. Watching television become ritual for the audiences. Television in fact have negative impact. Therefore, the aim of this research is to gain descriptive data about how is the pattern of television consumption in Denpasar. The research was quantitative research by using questionnaire. The research came out that audiences choose to watch television in finding information and entertainment. But Denpasar’s audiences were not categorizes in heavy viewers. The most favorite program is sinetron and news. For that television’s programs should be educated and informative.
Keywords: television consumption, audiences, denpasar, television’s program